Turbidity removal by mucilage from Basella alba - Hoang Oanh, Le Thi; Lan Anh, Nguyen Thi; Huong, Pham Lan; Nam, Ha Xuan; Loan, Luu Minh (Vietnam Journal of Science and Technology, 2020)
Coagulation and flocculation are preliminary used in water treatment processes for turbidity removal, using popularily synthetic chemicals with health and environmental concerns. The use of natural flocculants has known to be a promising alteratives for chemical ones due to their environmental friendly behavior. This research investigated turbidity removal efficiency of mucilage extracted from Basella alba - an indigenous species in Vietnam - in the role of a flocculant. The removal efficiency of mucilage was investigated in combination with PAC or Alum on To Lich river water by mean of Jar tests. PAC or Alum alone can remove maximum 97% and 90% turbidity of To Lich river water at its original pH for the sedimentation time of 30 minutes. The combination of mucilage and PAC or Alum increased the efficiencies of turbidity removal and reduced the amount of chemicals needed. The corresponding increases were maximum 7% and 18%, respectively; while the reduction of PAC/Alum used was 75-80%.